Initial investigation into patellofemoral morphology in hemophilic arthritis patients - Wang, Haohao; Jiang, Rendong; Dong, Zhishang; Zhao, Dongyue; Zhao, Jianli; Shi, Chao; Yuan, Zhen (Frontiers in Surgery, 2024)
BackgroundHemophilic arthritis (HA) is associated with significant changes in the morphology of mature knee joints due to abnormal growth plate development. Previous studies have established marked distinctions between the femur and tibia of subjects with Haemophilia and those with osteoarthritis (OA). This study explored the morphological characteristics of the patella and patellofemoral joint in subjects with Haemophilia. These findings can inform the design of knee joint prostheses tailored to this condition, improve the precision of total knee replacement surgery, and reduce postoperative knee pain and patellar dislocation.MethodsBefore surgery, we conducted preoperative measurements of patellar length, patellar diagonal length, patellar ligament length, patellar width, patellar thickness, the INSALL index, the lateral patellofemoral angle, the trochlear groove angle,the patellar lateral displacement rate, and the patellofemoral index using lateral and axial x-ray images in 40 subjects with Haemophilia, 40 OA patients, and 40 normal individuals.ResultsSignificant statistical differences in certain morphological parameters were observed among the three groups of patients (P < 0.05). Compared with the OA and normal control groups, the HA group presented significant disparities in patellar thickness, patellar ligament length, the Insall ratio, the patellar lateral shift rate, the lateral patellar angle, and the patellofemoral index.ConclusionCompared with OA and normal individuals, Subjects with Haemophilia presented with smaller and thinner patellae, more significant patellar ligament contracture, reduced patellar height, and more pronounced patellar dislocation. Consequently, during total knee arthroplasty, we lean toward patellar reshaping in subjects with Haemophilia, exercise caution when considering patellar replacement, and, for those with severe preoperative patellar dislocation, perform intraoperative lateral retinacular release.